The characterisation of the in vitro metabolism and transport of 6-hydroxykynurenic acid, an important constituent of Ginkgo biloba extracts. (4th May 2021) - Talap, Jadera; Shen, Zhuowei; Nie, Jing; Pan, Jie; Xu, Mingcheng; Zeng, Kui; He, Kaifeng; Ou, Fengting; He, Houhong; Yao, Jianbiao; Wang, Ruwei; Yu, Lushan; et al.
Abstract: 6-Hydroxykynurenic acid (6-HKA) is a nitrogen-containing phenolic acid compound in Ginkgo biloba leaves. The pharmacological activities of 6-HKA have been reported and shown that 6-HKA has the potential to become a therapeutic drug and may play an important role in the treatment of nervous system diseases. However, there are few studies on the drug metabolism and transport of 6-HKA. The aim of this study is to investigate the in vitro metabolism of 6-HKA and its interaction with multiple important drug transporters. The in vitro metabolism experiments in the present study demonstrate that 6-HKA might not undergo phase-I or phase-II metabolism in hepatic microsomes/S9 of rats. In addition, some drug transporters, including OAT1/3, OCT2, MDR1, OATP1B1, MATE1/2K and OCTN2, were investigated. The cellular uptake assays indicate that 6-HKA exhibits inhibition to the transport of classical substrates mediated by OAT3, OCT2, MATE2K and OCTN2 but has no significant effect on the transport of substrates mediated by MDR1, OAT1, OATP1B1 or MATE1. Further investigation of cellular accumulation assays shows that 6-HKA might be the substrate of OAT3, but not OCT2 or OCTN2. The bidirectional transport study suggests that 6-HKA is not a substrate of MDR1. The information about the in vitro metabolism of 6-HKA and the interaction between 6-HKA and some transporters will help us to better understand the pharmacokinetic properties of 6-HKA and provide reference for its pharmacodynamics, DDIs and drug-food interactions studies.